Susceptibility of Bacteria Infecting Urinary Tract to Some Antibiotics and Essential Oils - Mohamed T. Shaaban, Hanan A. Ghozlan, Marwa M. El Maghraby (Journal of Applied Pharmaceutical Science)
This study investigates the most common urinary tract infection bacteria and their sensitivity to antibiotics and some essential oils from Egyptian plants. The Urinary tract bacteria were sampled from patients expressing any symptoms of urinary tract infection except those taking antibiotics. The bacteria were isolated, cultured, and identified. 64 bacterial isolates were identified as E.coli (28 isolates), Klebsiella pneumonia (9 isolates) Pseudomonas aeruginosa (6 isolates), Proteus mirabilis (6 isolates), Staph.aureus (5 isolates) , Enterococcus faecalis (4 isolates), Morganella morganii ( 4 isolates ) and Pseudomonas fluorescens (2 isolates). The isolates showed different degrees of sensitivity to different antibiotics . Among the essential oils of five medical plants known for their application in folk medicine in Egypt , oil of Dill (Anethum graveolens ) showed the highest effect , affecting more than 50 % of both gram +ve and gram –ve bacteria ,followed by Parsley (Petroselinum hortense) and Celery (Apium graveolens) affecting 48% & 41% of the isolates respectively . The oil of Thyme (Thymus valgare) was effective against Gram –ve bacteria only. The lowest effects were recorded to the oil of Chamomile (Marticaria recutita) affecting only 5% of the tested isolates.
Keywords: urinary tract infection, antibiotics, bacteria, essential oils.